Adolescents' Perceptions and Experiences of Their Responsibilities for Their Alcohol Use-A Group Interview Study - Mari A. Mynttinen; Kaisa E. Mishina; Mari K. Kangasniemi (MDPI AG, 2021)
Young people often experiment with alcohol during adolescence, which is a period of their life that is characterized by increasing responsibility. Knowing how adolescents perceive responsibilities with regard to their alcohol use could prevent their alcohol consumption and help them to take responsibility for this aspect of their lives. This study describes adolescents' perceptions and experiences of their responsibilities for alcohol use. We used a qualitative descriptive method that focused on 87 adolescents aged 14-16 years, from two schools. They took part in semi-structured interviews in 19 groups in Finland in 2017. The data were analyzed using inductive content analysis. The adolescents described alcohol as harmful, but tempting, and said that they were developing a sense of responsibility for their alcohol use. They were responsible for their own wellbeing, behaving responsibly if they drank and intervening in peers' alcohol use. They talked about how their parents had unquestionable responsibilities to care about whether adolescents drank alcohol. Their parents' responsibilities related to the guidance they gave, how strict they were and how they responded to adolescents using alcohol. Anonymous and intense support from authorities encouraged adolescents to learn to take responsibility. Identifying and focusing on their responsibilities could help adolescents to develop into healthy individuals and increase their awareness of the need to avoid alcohol. Parents may also need support to meet their responsibilities.